Characterization of biofilm-forming ability and antibiotic resistance profiles of clinical Pseudomonas aeruginosa isolates from patients with cystic fibrosis - M Anjaneya Swamy,; Kanumuru Balu Mahendran,; Nethala Ravi Kumar,; Ketha Venkateswarlu, (Asian Journal of Medical Sciences, 2024)
Background: Pseudomonas aeruginosa is a key pathogen in cystic fibrosis (CF) associated infections, known for its biofilm-forming ability and resistance to multiple antibiotics. Understanding the relationship between biofilm production and antibiotic resistance profiles in clinical isolates can guide treatment strategies. Aims and Objectives: The aims of this study were to investigate the biofilm-forming abilities and antibiotic resistance profiles of clinical P. aeruginosa isolates from patients with CF and to determine the relationship between these two factors and their impact on treatment efficacy. Materials and Methods: A cross-sectional study was conducted on 100 clinical isolates of P. aeruginosa from CF patients. Biofilm-forming capacity was categorized as strong, moderate, or weak based on quantitative assays. Antibiotic resistance was assessed for ciprofloxacin, tobramycin, ceftazidime, meropenem, and piperacillin/tazobactam. Multi-drug resistance was defined as resistance to three or more antibiotic classes. Statistical correlations between biofilm-forming capacity and resistance levels were evaluated using the Chi-square tests. Results: Fifty-six percentages of isolates were strong biofilm producers, while 34% and 10% were moderate and weak producers, respectively. The highest antibiotic resistance was observed against ciprofloxacin (60%), followed by tobramycin (50%) and ceftazidime (45%). Forty percentages of the isolates were classified as multi-drug resistant. Strong biofilm producers demonstrated a significantly high correlation with antibiotic resistance (P<0.05). Two predominant clonal groups were identified among the isolates, suggesting a possible clonal spread of resistance traits. Conclusion: The study confirms a strong association between robust biofilm production and heightened antibiotic resistance in P. aeruginosa isolates from CF patients. These findings highlight the need for targeted therapeutic strategies to disrupt biofilm formation and curb resistance spread.